Cardiovascular risk and mortality in rheumatoid arthritis compared with diabetes mellitus and the general population. (27th September 2020) - Løgstrup, Brian B; Ellingsen, Torkell; Pedersen, Alma B; Darvalics, Bianka; Olesen, Kevin K W; Bøtker, Hans Erik; Maeng, Michael
Abstract: Objectives: To compare risk of cardiovascular disease and mortality in patients with incident RA, diabetes mellitus (DM) and the general population (GP). Methods: Patients diagnosed with incident RA were matched 1:5 by age, sex and year of RA diagnosis with the GP. In the same period, patients with incident DM were included. Outcomes were heart failure (HF), myocardial infarction (MI), coronary revascularization, stroke, major adverse cardiovascular events (MACE) and death up to 10 years after diagnosis. Results: We included 15 032 patients with incident RA, 301 246 patients with DM and 75 160 persons from the GP. RA patients had an increased risk of HF [hazard ratio (HR) 1.51, 95% CI: 1.38, 1.64], MI (HR 1.58, 95% CI: 1.43, 1.74), percutaneous coronary intervention (PCI; HR 1.44, 95% CI: 1.27, 1.62), coronary artery bypass grafting (CABG; HR 1.30, 95% CI: 1.05, 1.62) and stroke (HR 1.22, 95% CI: 1.12–1.33) compared with the GP. However, the 10-year all-cause mortality was at the same level as observed in the GP. Cardiac death and MACE were increased in RA compared with the GP. When compared with patients with DM, RA patients had a lower adjusted risk of HF (HR 0.79, 95% CI: 0.73, 0.85), CABG (HR 0.62, 95% CI: 0.51, 0.76) and stroke (HR 0.82, 95% CI: 0.76, 0.89), and similar risk of MI and PCI. DM patients had the highest risk of 10-year mortality, cardiac death and MACE. Conclusion: This study demonstrates that RA is associated with an increased risk of HF, MI, stroke and coronary revascularization than found in the GP but without reaching the risk levels observed in DM patients.